Encyclopedia of television - Newcomb, Horace (Fitzroy Dearborn, 2004)
Presents hundreds of alphabetized, cross-referenced articles on various aspects of television including series, networks, genres, actors, journalists, writers, and technology, covering the U.S. and Canada. This volume comprises S-Z.